Preference Organization Analysis on The NCT Show: Music Space with Johnny and Mark (Universitas Pamulang, 2025)
This research uses conversation analysis to dig deeper into human conversation, especially in the context of talk show. The main purpose of this research is to examine the types and strategies of preference organization used by participants in talk shows. The theory used is Levinson’s preference organization theory. The research method applied is a descriptive qualitative method. The result of this research is that there are 61 data found, with a distribution of 5 request data, 4 invite data, 33 assessment data, 18 question data, and 1 blame data. In conclusion, preferred responses are dominant in this talk show. The large number of preferred responses in the talk show indicates a generally positive and cooperative communication environment. This is due to the close relationship between the participants. They share the same knowledge of the topic of discussion.